Pekić’s paradoxology and Serbian identity - Stanojević, Dobrivoje (Sociološki pregled, 2025)
In this paper, the author approaches the research of Borislav Pekić’s poetics of paradoxology in the novel Golden Fleece from a stylistic and rhetorical point of view. Pekić’s search for Serbian identity, with a special reference to immanent paradoxology in this novel, was achieved through a series of related ironic-parodical procedures that lead to a deeper insight into the changes and the constants of Serbian identity. The research into Pekić’s poetics of paradoxicality when dealing with the topic of Serbian identity is based on methods of interpretation that can reach the artistic and cultural meaning of the writer’s civilizational insights. This Serbian writer permeates and nuances shorter genres in the light of paradoxes and neo-aphoristic microstructural units with a distinct polemic approach and a humorous charge that help a more complete understanding of the hero’s Serbian identity. The novel Golden Fleece is organized as a complex intellectual and argumentative discourse about the basic manifestations of Serbian identity in different historical and social circumstances. The paper is concluded with an insight into the importance of the elements of grotesque optimism and “cheerful scepticism” as the basic poetic templates of this complex novelistic discussion about Serbian identity. The study of Pekić’s paradoxology helps with broader insights into the specific features of Serbian identity. In this manner, the nature and logic of historical events in the Serbian past and present can be understood in a more profound way.